Online Fraud Risk and Its Impact on Student Trust in Digital Financial Services - Lauron, Kathleen Grace M.; Malinao, Brigette Rose E.; Detecio, Chris James T.; Abejero, Edward Louie Y.; Genon, Patricia Andrea A.; Abarquez, Paulino Jr. F.; Malubay, Ryan B.; Narsico, Peter G. (Future Science / FSH-PH Publications, 2026)
In this study we have investigated the impact of digital financial risk perception on customer trust in digital financial services on students at a university in Cebu City of the Philippines. As people increasingly depend on e-wallets and mobile banking to transact daily business, it is important to learn how fraud awareness influences their trust. We have used a quantitative correlational design and conducted a Likert scale survey on 310 students. The Likert scale is not too reliable (Cronbach’s α = 0.778) but students found online fraud to be a serious and growing problem (M = 3.37). However, they trusted digital financial services (M = 2.92). Simple linear regression revealed that perceived online fraud risk is not a strong predictor of customer trust (R² = 0.003 and p = 0.34), indicating that fraud awareness is not responsible for all the variation in trust. These results suggest that students are more trusting in functional trust (convenience, usability and platform performance) than in perceived safety. Despite high-risk awareness, students continue to use digital financial services because those services are essential to daily life. This finding indicates that service providers need to better serve the customers when it comes to platform reliability, user experience and customer support as these properties seem to be more important in maintaining trust than perceived fraud risk. Future research should also look at user satisfaction, digital literacy and actual fraud experience and longitudinal design to track how trust changes with changing digital practices.